2016
DOI: 10.1093/cercor/bhv335
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Cannabinoid Exposure Induces a Persistent Sub-Cortical Hyper-Dopaminergic State and Associated Molecular Adaptations in the Prefrontal Cortex

Abstract: Considerable evidence suggests that adolescent exposure to delta-9-tetrahydrocanabinol (THC), the psychoactive component in marijuana, increases the risk of developing schizophrenia-related symptoms in early adulthood. In the present study, we used a combination of behavioral and molecular analyses with in vivo neuronal electrophysiology to compare the long-term effects of adolescent versus adulthood THC exposure in rats. We report that adolescent, but not adult, THC exposure induces long-term neuropsychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 68 publications
9
107
2
Order By: Relevance
“…This type of cognitive filtering is often indexed in rodent studies via assessing the reduction in startle response to a loud tone when that stimulus is immediately preceded by a weaker, non-startle-inducing tone – a phenomenon known as pre-pulse inhibition (PPI). Long-term deficits in PPI have been frequently observed in rodent studies after CB exposure during adolescence, but not when animals received equivalent exposure in adulthood (e.g., Renaud et al, 2016), supporting the association of CB action on the adolescent brain with the later induction of schizophrenia-like alterations.…”
Section: Cannabinoidsmentioning
confidence: 95%
See 2 more Smart Citations
“…This type of cognitive filtering is often indexed in rodent studies via assessing the reduction in startle response to a loud tone when that stimulus is immediately preceded by a weaker, non-startle-inducing tone – a phenomenon known as pre-pulse inhibition (PPI). Long-term deficits in PPI have been frequently observed in rodent studies after CB exposure during adolescence, but not when animals received equivalent exposure in adulthood (e.g., Renaud et al, 2016), supporting the association of CB action on the adolescent brain with the later induction of schizophrenia-like alterations.…”
Section: Cannabinoidsmentioning
confidence: 95%
“…Several studies have observed reductions in social behavior (O’Shea et al, 2004, 2006; Schneider, 2008; Schneider et al, 2008; Realini et al, 2011), perhaps associated in part with decreases in social motivation (Renaud et al, 2016) and increases in social anxiety (O’Shea et al, 2004, 2006). Social anxiety has occasionally (O’Shea et al, 2006; Quinn et al, 2008) but not typically (O’Shea et al, 2004; Schneider, 2008; Schneider et al, 2008) been reported after equivalent CB exposure in adulthood.…”
Section: Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the ability of CBD to inhibit mesolimbic DAergic activity and blunt fearrelated memory formation is particularly intriguing given the large body of evidence demonstrating that the primary psychoactive phytochemical in cannabis, THC, produces propsychotic effects (Kuepper et al, 2011). Furthermore, in direct contrast to the effects of CBD, THC has been shown to induce a state of hyperactive mesolimbic DAergic activity following adolescent neurodevelopmental exposure (Renard et al, 2016a). In addition, we have recently reported that intra-NASh CBD blocks hyper-DAergic activity and psychomotor sensitization induced by amphetamine exposure (Renard et al, 2016b).…”
Section: Implications Of Cbd's Modulatory Role On Mesolimbic Activitymentioning
confidence: 99%
“…In terms of psychotropic profiles, THC is associated with transient and long-term psychotomimetic effects Murray et al, 2007), whereas clinical and preclinical research has shown that CBD can produce antipsychotic and anxiolytic effects (Crippa et al, 2011;Campos et al, 2012;Fogaca et al, 2014;Zuardi et al, 2006Zuardi et al, , 2012Mechoulam et al, 2007;Leweke et al, 2012;Renard et al, 2016a;Schubart et al, 2014;Gomes et al, 2015). In addition, CBD may modulate emotional memory processing and decrease symptoms associated with emotional memory disorders such as post-traumatic stress disorder (PTSD; Blessing et al, 2015,Betthauser et al, 2015.…”
Section: Introductionmentioning
confidence: 99%